2014
DOI: 10.1128/aac.02446-14
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol-Based Hydrogels for Controlled Release of the Antimicrobial Subtilosin for Prophylaxis of Bacterial Vaginosis

Abstract: c Current treatment options for bacterial vaginosis (BV) have been shown to be inadequate at preventing recurrence and do not provide protection against associated infections, such as that with HIV. This study examines the feasibility of incorporating the antimicrobial peptide subtilosin within covalently cross-linked polyethylene glycol (PEG)-based hydrogels for vaginal administration. The PEG-based hydrogels (4% and 6% [wt/vol]) provided a two-phase release of subtilosin, with an initial rapid release rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In a model study with nisin and Micrococcus luteus , one of the most sensitive reference microorganisms, it was shown that the most effective inhibition occurs when an initial phase of fast release is followed by a phase of slow release in smaller quantities, just enough to control the remaining population [45]. While appropriate food-grade delivery systems are still under investigation, they are available for a variety of pharmaceutical applications [46].…”
Section: Bacteriocins: Applications Are Determined By the Functionsmentioning
confidence: 99%
“…In a model study with nisin and Micrococcus luteus , one of the most sensitive reference microorganisms, it was shown that the most effective inhibition occurs when an initial phase of fast release is followed by a phase of slow release in smaller quantities, just enough to control the remaining population [45]. While appropriate food-grade delivery systems are still under investigation, they are available for a variety of pharmaceutical applications [46].…”
Section: Bacteriocins: Applications Are Determined By the Functionsmentioning
confidence: 99%
“…Microbicide-loaded hydrogels have been studied for sustained vaginal drug delivery, since in some clinical trials the maintenance of therapeutic drug concentrations for a prolonged period is essential. Sundara et al demonstrated the potential application of subtilosin-containing polyethylene glycol hydrogels for BV prophylaxis [ 17 ]. The hydrogels displayed an initial rapid-release phase (24 h) followed by a slow, sustained-release phase.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is an increasing interest in exploring antibacterial surfaces, which not only prevent infection but also helps in circumventing antibacterial resistance. Biomaterials like gels and hydrogels, with unique capability to hold water, have immense potential in such applications. …”
Section: Introductionmentioning
confidence: 99%